Handbook of food structure development - Spyropoulos, Fotios; Lazidis, Aris; Norton, Ian T. (Royal Society of Chemistry, 2020)
The most useful properties of food, i.e. the ones that are detected through look, touch and taste, are a manifestation of the food's structure. Studies about how this structure develops or can be manipulated during food production and processing are a vital part of research in food science. This book provides the status of research on food structure and how it develops through the interplay between processing routes and formulation elements. It covers food structure development across a range of food settings and consider how this alters in order to design food with specific functionalities and performance. Food structure has to be considered across a range of length scales and the book includes a section focusing on analytical and theoretical approaches that can be taken to analyse/characterise food structure from the nano- to the macro-scale. The book concludes by outlining the main challenges arising within the field and the opportunities that these create in terms of establishing or growing future research activities. Edited and written by world class contributors, this book brings the literature up-to-date by detailing how the technology and applications have moved on over the past 10 years. It serves as a reference for researchers in food science and chemistry, food processing and food texture and structure.
Includes index.
Keywords: Food -- Analysis -- Handbooks, manuals, etc.; Food -- Composition -- Handbooks, manuals, etc.; elektronické knihy; electronic books